2013
DOI: 10.1071/bt13259
|View full text |Cite
|
Sign up to set email alerts
|

Effect of forest fragmentation and altitude on the mating system of Eucalyptus pauciflora (Myrtaceae)

Abstract: Habitat fragmentation is a key factor causing variation in important mating system parameters in plants, but its effect is variable. We studied mating system variation among 276 native trees from 37 populations of Eucalyptus pauciflora from Tasmania. We assayed 10 microsatellite loci from 1359 open-pollinated progeny from these trees. Across Tasmania the species’ mating system was characterised by a high outcrossing rate (tm = 0.90) but moderate bi-parental inbreeding (tm–ts = 0.16) and moderate correlated pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 83 publications
1
10
0
Order By: Relevance
“…The most likely explanation for the observed pattern is that trees in small populations receive lower quality pollen through higher proportional transfer of self-pollen. Although we found no decline in effective outcrossing rate, the likelihood of increased selfing in small populations is consistent with evidence from other Eucalyptus species that incomplete pre-or post-zygotic ovule abortion mechanisms typically lead to reduced seed set when faced with increased self-pollination (Griffin et al, 1987;Ellis and Sedgley, 1992;Kennington and James, 1997;Pound et al, 2003;Krauss et al, 2007;Gauli et al, 2014). In addition, the very high rates of pollen immigration into small E. wandoo populations ) appear insufficient to mitigate the impact of high selfing rates on seed set.…”
Section: Reproductive Output and Small Population Processessupporting
confidence: 69%
See 1 more Smart Citation
“…The most likely explanation for the observed pattern is that trees in small populations receive lower quality pollen through higher proportional transfer of self-pollen. Although we found no decline in effective outcrossing rate, the likelihood of increased selfing in small populations is consistent with evidence from other Eucalyptus species that incomplete pre-or post-zygotic ovule abortion mechanisms typically lead to reduced seed set when faced with increased self-pollination (Griffin et al, 1987;Ellis and Sedgley, 1992;Kennington and James, 1997;Pound et al, 2003;Krauss et al, 2007;Gauli et al, 2014). In addition, the very high rates of pollen immigration into small E. wandoo populations ) appear insufficient to mitigate the impact of high selfing rates on seed set.…”
Section: Reproductive Output and Small Population Processessupporting
confidence: 69%
“…Mating system studies have shown that increased within-plant foraging and reduced local mate availability appears to affect pollen quality in fragmented populations of many eucalypts and other Myrtaceae, resulting in reduced seed set (Krauss et al, 2007;Yates et al, 2007b;Gauli et al, 2014), while late-acting selfincompatibility mechanisms may have prevented outcrossing rates from being significantly affected by fragmentation in many species (Ottewell et al, 2009;Gauli et al, 2014;Breed et al, 2015), but not all (Butcher et al, 2005;Mimura et al, 2009;Breed et al, 2015). Despite changes in pollen quality, the level of pollination and pollinator abundance was unchanged in Calothamnus quadrifidus (Yates et al, 2007a), while honeybees have increased (González-Varo et al, 2009) or decreased (Hingston et al, 2004) pollination rates in some species of Myrtaceae.…”
Section: Introductionmentioning
confidence: 99%
“…However, this rate is very low compared to widespread eucalypts (Millar et al 2000;Byrne 2008;Mimura et al 2009;Bradbury and Krauss 2013;Breed et al 2015a, b) but comparable with, or lower than, some other rare and restricted species (Butcher et al 2005;Sampson and Byrne 2015). Eucalypts often maintain high outcrossing rates in seed progeny despite small population size or even clonality, due to post-zygotic barriers against inbreeding and selection in the seed capsule acting against selfed seeds (James and Kennington 1993;Gauli et al 2013). However, these processes do not appear to be strong in E. absita, which displayed one of the lowest rates of outcrossing reported for eucalypts, which may also have been artificially inflated by the presence of hybrid outcrosses in seedling progeny.…”
Section: High Rates Of Inbreeding In Seed Cropsmentioning
confidence: 94%
“…We have also tried to reduce the risk of sampling climatically matched seed sources which may have poor seed crops or exhibit inbreeding depression by flagging seed sources likely to be in fragmented landscapes. Reduced reproductive output, reduced outcrossing rates, and increased inbreeding depression are often syndromes of fragmented and small populations (Young et al ), including Eucalyptus (Borralho & Potts ; Mimura et al ; Gauli et al ). However, such effects may be species‐specific (Breed et al ; Gauli et al ) and dependent on pollinator mobility (Aguilar et al ; Kramer et al ).…”
Section: Discussionmentioning
confidence: 99%